Decade of variable progress: trends in fatal injury in workers in New Zealand from a national observational study. (26th October 2020) - Lilley, Rebbecca; Maclennan, Brett; Davie, Gabrielle; McNoe, Bronwen M; Horsburgh, Simon; Driscoll, Tim R
Abstract : Introduction: Analyses of secular trends in work-related fatal injury in New Zealand have previously only considered the total working population, potentially hiding trends for important subgroups of workers. This paper examines trends in work-related fatalities in worker subgroups between 2005 and 2014 to indicate where workplace safety action should be prioritised. Methods: A dataset of fatally injured workers was created; all persons aged 15–84 years, fatally injured in the period 2005–2014, were identified from mortality records, linked to coronial records which were then reviewed for work relatedness. Poisson regression modelling was used to estimate annual percentage change in rates by age, sex, ethnicity, employment status, industry and occupation. Results: Overall, worker fatalities decreased by 2.4% (95% CI 0.0% to 4.6%) annually; an average reduction of 18 deaths per year from baseline (2005). Significant declines in annual rates were observed for younger workers (15–29 and 30–49 years), indigenous Māori, those in the public administration and service sector, and those in community and personal service occupations. Increases in annual rates occurred for workers in agriculture and forestry and fisheries sectors and for labourers. Rates of worker deaths in work-traffic settings declined faster than in workplace settings. Discussion: Although overall age-standardised rates of work-related fatal injury have been declining, these trends were variable. Sources of injury risk in identifiable subgroups with increases in annual rates need to be urgently addressed. This study demonstrates the need for regular, detailed examination of the secular trends to identify those subgroups of workers requiring further workplace safety attention.